The impact of automation on the safety of drug dispensing in nursing homes - Idoia Beobide-Tellería (Farmacia Hospitalaria, 2018)
Objective: To compare the rate and severity of reported dispensing errors in nursing homes using manual medication dispensation vs automated dispensation with a specifically selected Automated Dispensing System.Method: A pre-post retrospective observational study conducted in 7 nursing homes. Comparison of voluntarily reported dispensing errors in 2 periods under a manual dispensing system of weekly pill boxes (data from 2013) and an Automated drug dispensing and Packaging System Xana 4001U2 Tosho® for oral solid medications used in combination with a manual system for other drug forms (data from 2015). We analysed patient function, cognition, and pharmacological data from both periods.Results: The residents’ mean age (83.9 vs 83.6 years; P > .05) and physical functioning (Barthel index 41.8 vs 44.2; P > .05) were similar, but not their level of cognitive functioning (MMSE 20.3 vs 21.7; P < .05). During 2013 (manual system) 408 errors were detected, whereas in 2015 (automated system) only 36 were detected. This represents a reduction of 91% in dispensing errors. A total of 43 errors reached the patient in 2013 vs 6 errors in 2015. Of these, 5 errors vs 1 error, respectively, required monitoring.Conclusions: The introduction of an Automated drug dispensing and Packaging System significantly improves safety in the dispensing and administration of solid medications in nursing homes. The voluntary reporting of errors facilitated comparisons of safety during the 2 periods under different dispensing systems.